Rasch analysis of the new general self efficacy scale: an evaluation of its psychometric properties in older adults with low vision - Micaela Gobeille; Ava K. Bittner; Alexis G. Malkin; Jeffrey Ho; Cecilia Idman-Rait; Max Estabrook; Nicole C. Ross; for the CARE Study Team (Health and Quality of Life Outcomes, 2024)
Abstract Background While general self-efficacy is known to relate to achievement in many areas, it has rarely been evaluated in individuals with low vision. Here we explore the psychometric properties and targeting of the New General Self Efficacy Scale (NGSES) using Rasch analysis in data collected from older adult clinical trial participants with low vision. Methods Participants (n = 121) completed pre-intervention telephone questionnaires (i.e., NGSES, Activity Inventory (AI), Beck Depression Inventory (BDI), SF-36, and the Telephone Interview for Cognitive Status (TICS). Rasch analysis using the Method of Successive Dichotomizations (MSD) was applied to NGSES, AI, and BDI datasets to estimate person and item measures, and ordered rating category thresholds. NGSES infit mean square statistics and standard errors were analyzed to test whether data fit Rasch model requirements, and targeting was assessed by comparing distributions of person and item measures. Multiple linear regression evaluated the influence of participant characteristics on NGSES person measures. Results There was a significant difference (p = 0.01) in the distributions of NGSES person measures (mean = 0.85, range -2.1-3.2) and item measures (mean = 0, range -1.0-0.72). Infit mean square statistics and standard errors for item and person measures conformed to expectations of the Rasch model. Greater NGSES person measure was related to lower BDI person measure (β = -0.48, p < 0.0005, 95% CI -0.67—-0.28) and higher AI person measure (β = 0.11, p = 0.047, 95% CI 0.0013 – 0.22) after controlling for cognitive status (TICS). Other variables including SF-36, visual acuity, and patient demographics were not related to NGSES person measure. Conclusions While NGSES person measures estimated from a low vision patient population conformed to basic Rasch model requirements, the significant differences in the person and item measure distributions indicate poor NGSES targeting, specifically a ceiling effect. Therefore, there is limited discrimination between persons at the upper end of the scale. While further work can evaluate how self-efficacy may be associated with other factors in the low vision patient population, the ceiling effect found in this study cautions interpretation of NGSES results for those with high general self-efficacy. Trial registration Pre-registered on clinicaltrials.gov, identifier NCT04926974.